2011
DOI: 10.1159/000334517
|View full text |Cite
|
Sign up to set email alerts
|

Loss of <i>R-Spondin1</i> and <i>Foxl2</i> Amplifies Female-to-Male Sex Reversal in XX Mice

Abstract: In vertebrates, 2 main genetic pathways have been shown to regulate ovarian development. Indeed, a loss of function mutations in Rspo1 and Foxl2 promote partial female-to-male sex reversal. In mice, it has been shown that the secreted protein RSPO1 is involved in ovarian differentiation and the transcription factor FOXL2 is required for follicular formation. Here, we analysed the potential interactions between these 2 genetic pathways and have shown that while Rspo1 expression seems to be independent of Foxl2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 167 publications
2
58
0
1
Order By: Relevance
“…In the mouse, Foxl2 is the earliest known ovarian marker, its expression being detectable from 12.0 d.p.c. (Auguste et al 2011). Nevertheless, Foxl2 K/K mice develop normally until birth, and no perinatal sex reversal is observed (Schmidt et al 2004, Uda et al 2004.…”
Section: Sex Determination and Early Ovarian Developmentmentioning
confidence: 99%
“…In the mouse, Foxl2 is the earliest known ovarian marker, its expression being detectable from 12.0 d.p.c. (Auguste et al 2011). Nevertheless, Foxl2 K/K mice develop normally until birth, and no perinatal sex reversal is observed (Schmidt et al 2004, Uda et al 2004.…”
Section: Sex Determination and Early Ovarian Developmentmentioning
confidence: 99%
“…In the embryonic mouse ovary, Foxl2 expression is partly dependent on RSPO1 and CTNNB1 (Manuylov et al 2008, Auguste et al 2011, whereas it is normally expressed in the Wnt4 K/K ovary (Manuylov et al 2008), suggesting that Foxl2 is expressed in two different somatic cell populations. Moreover, simultaneous deletion of Foxl2 K/K and Wnt4 K/K , as well as Foxl2…”
Section: Rspo1 Wnt4 and Foxl2 Relationship In Ovarian Developmentmentioning
confidence: 99%
“…and Rspo1 K/K , promotes early female-to-male sex reversal (Ottolenghi et al 2007, Auguste et al 2011, indicating that Foxl2 and Rspo1/Wnt4 have Figure 2 Role of Rspo1 and Wnt4 during sexual differentiation. During embryonic development of WT ovaries (top), Rspo1 expression by somatic cells at 12.5 dpc first induces the proliferation, then differentiation of female germ cells into oogonia at 12.5 and 14.5 dpc respectively (pink arrows).…”
Section: Rspo1 Wnt4 and Foxl2 Relationship In Ovarian Developmentmentioning
confidence: 99%
“…Originally, the FOXL2 gene was considered to play a role in the sex determination and generation of sex-reversal phenotype in goat (Auguste et al, 2011;Boulanger et al, 2014). In addition, previous studies have shown that a somatic missense mutation in the FOXL2 gene, which is expressed in the ovary, have a high correlation to granulosa cell tumors (Schmidt et al, 2004;Gustin et al, 2016).…”
Section: Discussionmentioning
confidence: 99%